In vivo self‐gated 23Na MRI at 7 T using an oval‐shaped body resonator - Platt, Tanja; Umathum, Reiner; Fiedler, Thomas M.; Nagel, Armin Michael; Bitz, Andreas K.; Maier, Florian; Bachert, Peter; Ladd, Mark E.; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich; Behl, Nicolas G. R. (Magnetic resonance in medicine, 2018)
Purpose - This work faces three challenges of sodium (23Na) torso MRI on the way to quantitative 23Na MRI: Development of a 23Na radiofrequency transmit and receive coil covering a large part of the human body in width and length for 23Na MRI at 7 T; reduction of blurring due to respiration in free‐breathing 23Na MRI using a self‐gating approach; and reduction of image noise using a compressed‐sensing reconstruction.
Im Titel ist 23 hochgestellt
Gesehen am 23.04.2020